Fibrofolliculomas in Birt-Hogg-Dubé Syndrome treated with a CO2 and dye laser combination: a case report and literature review - Giuseppe Lodi; Giovanni Cannarozzo; Mario Sannino; Laura Pieri; Irene Fusco; Francesca Negosanti (PAGEPress Publications, 2024)
The Birt-Hogg-Dubé Syndrome (BHDs) can cause benign skin lesions like fibrofolliculomas as well as additional systemic symptoms like pulmonary cysts, kidney tumors, and recurrent pneumothoraces. We report the successful treatment of fibrofolliculomas in a patient with BHDs using a combination of fractionated ablative CO2 laser and a Flash Lamp Pulsed Dye Laser (FPDL). This combined method improves the CO2 healing process's functional and cosmetic results; while the first wavelength (ablative) has a greater capacity for excision and tissue regeneration, the second wavelength (non-ablative) provides more control over the tissue healing process. The lesions were successfully ablated up to the papillary dermis without leading to an enhancement in the overall textural appearance. Therefore, deeper laser ablations may be able to stop dermal residual lesion relapses. In conclusion, fractionated CO2 laser and FPDL can be used safely and effectively to reduce the appearance of facial hamartomas related to BHDs.